Universal Tropes and Salvation Hopes: Making Up "International" Music Students in the International Baccalaureate Diploma Programme - Ben, Antía González (Teachers College record (1970), 2021)
Background/Context: Since the 1980s, the International Baccalaureate (IB) has gained popularity as an alternative to traditional public curricula, which public discourse frames as ill-equipped to prepare students for today's global market economy. Within this set of discourses, the IB emerges as a pedagogical tool for producing a new kind of "international" student who transcends the limitations of the traditional public school student. Purpose/Objective/Research Question/Focus of Study: Using the IB's high school music curriculum, known as the Diploma Programme (DP), as an entry point, this article examines the kind of "international" student that the IB claims to produce. Research Design: Informed by Foucault's notion of discursive subjectification, this study examines how the diploma music curriculum fabricates a particular kind of person: the diploma music student. Although the IB takes this subject position for granted, this study rests on the premise that diploma music students only become "thinkable" as such within certain sociohistorical conditions. Data Collection and Analysis: I engage with a set of official IB documents designed to inform the practice of DP music teachers. I approach this literature as a power-laden dispositive of knowledge production. I examine statements that relate to the construct of the diploma music student based on both the possibilities they afford and the meanings they preclude. I pay special attention to how this curriculum fabricates divisions, distinctions, and comparisons. Findings/Results: I argue that the IB's conception of the diploma music student as an independent thinker, an internationally minded person, and an individual committed to creating a better world reflects three cultural theses that coalesced during the European Enlightenment--the notions of reason, the nation, and progress. Through their recurrent treatment as "truth claims," these tropes become naturalized. They enable the IB's notion of the diploma music student to emerge discursively as neutral and universal. Conclusions/Recommendations: By pointing out some of the onto-epistemic systems that undergird the IB's conception of the diploma music student, I do not suggest that the IB should completely abandon those constructs. However, this curriculum's portrayal of modern Euro-American ways of being and thinking as universal is incompatible with its stated claims of ontological and epistemic universality and inclusivity. Alternatively, I suggest engaging with various ways of being and reasoning substantially and respectfully. In addition, it would be pertinent to consider how each onto-cosmo-epistemological system relates to other systems and the students vis-à-vis ongoing power-knowledge dynamics.